Ask a question

Find the inverse Laplace transform?

Find the inverse Laplace transform of F(s)=(2s+2)/(s^2+2s+5).

Answer: f(t)=2e^-t*cos 2t

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
David U. | Dave the Math TutorDave the Math Tutor
4.9 4.9 (238 lesson ratings) (238)
Check Marked as Best Answer

This problem can also be done without resorting to complex numbers.

Complete the square on the denominator:

          s2 + 2s + 5 = (s+1)2 + 4

Since the denominator is now expressed in terms of s+1, express the numerator the same way:

          2s + 2 = 2(s+1)

Now the whole fraction is in terms of s+1.  A Laplacian translation theorem says we can substitute "s" for "s+1" if we compensate by multiplying the inverse Laplacian by e-t:

         f(t) = L-1{2(s+1)/[(s+1)2 + 4]}

               = e-t L-1{2s/(s2 + 4)}

And the rest is easy:

          f(t) = 2e-t L-1{s/(s2 + 4)}

                = 2e-t cos(2t)

Grigori S. | Certified Physics and Math Teacher G.S.Certified Physics and Math Teacher G.S.

The denominator of the function has two complex roots:

                     s2 + 2s + 5 = (s+1+2i)(s+1 -2i)                                                            (1)


     F(s) = 2(s+1)/[(s + 1 +2i)(s+1 -2i)] = 2(s+1) {(-i/4) [ 2i/(s+1 -2i) - 2i/(s+1+2i)] =

    2(s+1)/{(1/2)[ 1/(s+1 -2i)    - 1/(s+ 1 +2i)].                                                            (2)

Now let's do thje following transformations:

  (s+1)/(s+1 -2i) = (s+1 - 2i +2i)/(s+1 - 2i) = 1 + 1/(s+1 -2i)   and

   (s+1)/(s+1 + 2i) = (s+1 + 2i - 2i)/(s+ 1+ 2i) = 1  - 1/(s+1 + 2i).

Now if you take the difference of the rational functions shown in  (2), you will obtain

                          F(s) = [1/(s+1 -2i)  - 1/(s+1 + 2i)]


                 L-1 F(s) = L-1 [1/(s+1 - 2i)]  - L-1 [1/(s+1 + 2i)]             (3)

You already know (from inverse transformation tables and your prior calculations) that

                                              L-1 (1/s-a)) = e at

If you substitute "a" by s+1-2i   one time and by s +1 + 2i in the second part of (3), then you will have

       L-1 F(s) =e (-1 +2i)t  + e(-1-2i)t  = 2e-t  [(e - 2it +e 2it)/2]                    (4)

But  the expression in parenthesis in (4) is cos 2t (use Muavre's formula to make sure that sin-s functions cancel each other). Thus, your answer is

                               f(t) = L-1 F(s) = 2 e-t cos (2t)                                      (5)

What about calculkating Laplace transforms using Texas instruments, I don't have TI - 89 to discuss available options. But I can find old versions of Texas instruments, and I'll try to figure it out later.

Good luck to you!